Prevalence and factors associated with sarcopenia and dynapenia in elderly people - Neves, Thiago (J Frailty Sarcopenia Falls, 2018)
OBJECTIVES: There is little information about the risk factors for sarcopenia and dynapenia. This study aimed to assess the prevalence of sarcopenia and dynapenia and to verify which risk factors are associated with the elderly population. METHODS: A total of 387 elderly people were evaluated. We used a questionnaire to identify socio-demographic and behavioral aspects. For physical performance, we used the Short Physical Performance Battery. Using the European Working Group of Sarcopenia in Older People consensus, we defined sarcopenia that includes the occurrence of low muscle mass, added to low muscle strength or low physical performance. Dynapenia was defined using handgrip strength. RESULTS: Sarcopenia and dynapenia were identified in 15.3% and 38.2% of the elderly people, respectively; 15.8% of women and 14.2% of men had sarcopenia, and 52.4% of women and 13.5% of men had dynapenia. Sarcopenia was associated with the increase in aging, white race, smoking, and risk of malnutrition. Dynapenia is more likely to occur in women and hospitalized patients. CONCLUSION: Sarcopenia had a greater association with the risk factors evaluated here, mainly with smoking and nutritional status. On the other hand, dynapenia was different, having a greater association with hospital intervention.